Pengurangan Risiko Musculoskeletal Disorder Melalui Perancangan Alat Bantu Meja Painting Menggunakan Metode REBA - Pradipta Sitompul, Kevin; Zufarshidqi, Ahnaf; Bintang Utama, Dhafiandra; Imdam, Irma Agustiningsih (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
PT.XYZ is an automotive company that produces various automotive components, one of which is the body reinforcement frame (Reinforce). The problem that arises occurs in the posture of workers who are not ergonomic in the painting process. This can lead to MSDs disease in the spine. The purpose of this research is to minimize the waste motion experienced by painting operators. The method used to minimize waste motion is Rapid Entire Body Assessment (REBA). From the results of this study obtained a REBA score of 7 which is classified as medium risk, to reduce the REBA score we propose designing a tool in the form of a painting table.